Nigeria : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper discusses further concrete steps to improve the governance of state-owned enterprise (SOE) and of the oil sector, given their importance to fiscal transparency and sustainability. Reducing leakages in the petroleum sector is especially macroeconomically critical, given Nigeria's current fiscal and external dependence on oil revenue. This paper provides an overview of developments, recent reforms, and challenges, and outlines policy recommendations for stronger governance and corruption prevention, detection, and resolution, including through anti-money laundering and combating the financing of terrorism measures that are useful beyond the petroleum sector. Strengthening transparency is needed to ensure that Nigeria receives maximum benefits from the oil and gas sector. The Nigerian authorities must accelerate their anti-corruption efforts to maintain momentum against both entrenched challenges and evolving threats. Achieving critical improvements to SOE governance and Anti-Money Laundering and Combating the Financing of Terrorism efforts will require a combination of legislative action, institutional reform, and additional resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet